Survival and Trends in Annualized Hazard Function by Age at Diagnosis Among Chinese Breast Cancer Patients Aged ≤40 Years: Case Analysis Study - Jun Wang; Ting Luo; Zhong-zheng Xiang; Ming-min He; Yuan-yuan Zeng; Tian Yang; Xiao-yuan Wei; Siting Yu; Ze-lei Dai; Ning-yue Xu; Chen-feng Tan; Lei Liu (JMIR Publications, 2023)
BackgroundYoung breast cancer patients are more likely to develop aggressive tumor characteristics and a worse prognosis than older women, and different races and ethnicities have distinct epidemiologies and prognoses. However, few studies have evaluated the clinical biological features and relapse patterns in different age strata of young women in Asia. ObjectiveWe aimed to explore survival differences and the hazard function in young Chinese patients with breast cancer (BC) by age. MethodsThe patients were enrolled from West China Hospital, Sichuan University. The chi-squared test, a Kaplan-Meier analysis, a log-rank test, a Cox multivariate hazards regression model, and a hazard function were applied for data analysis. Locoregional recurrence-free survival (LRFS), distant metastasis-free survival (DMFS), breast cancer-specific survival (BCSS), and overall survival (OS) were defined as end points. ResultsWe included 1928 young BC patients diagnosed between 2008 and 2019. Patients aged 18 to 25, 26 to 30, 31 to 35, and 36 to 40 years accounted for 2.7% (n=53), 11.8% (n=228), 27.7% (n=535), and 57.7% (n=1112) of the patients, respectively. The diagnosis of young BC significantly increased from 2008 to 2019. Five-year LRFS, DMFS, BCSS, and OS for the entire population were 98.3%, 93.4%, 94.4%, and 94%, respectively. Patients aged 18 to 25 years had significantly poorer 5-year LRFS (P<.001), 5-year DMFS (P<.001), 5-year BCSS (P=.04), and 5-year OS (P=.04) than those aged 31 to 35, 26 to 30, and 36 to 40 years. The hazard curves for recurrence and metastasis for the whole cohort continuously increased over the years, while the BC mortality risk peaked at 2 to 3 years and then slowly decreased. When stratified by age, the annualized hazard function for recurrence, metastasis, and BC mortality in different age strata showed significantly different trends, especially for BC mortality. ConclusionsThe annual diagnosis of young BC seemed to increase in Chinese patients, and the distinct age strata of young BC patients did not differ in survival outcome or failure pattern. Our results might provide strategies for personalized management of young BC.